Dispersal of young-of-the-year brown trout (Salmo trutta L.) from spawning beds : effects of parental contribution, body length and habitat - Andersson, Susanna (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2016)
Stocking of brown trout eggs Salmo trutta L. and construction of spawning beds are common measures in habitat restored streams. However, knowledge about how young-ofthe-year (YOY) trout disperse from stocking points and spawning beds, and how it relates to biotic and abiotic factors, are sparse. This study was conducted to explore dispersal differences among families, if dispersal is restricted to a limited area, if habitat characteristics have an impact on the dispersal, and if trout managers have to take YOY trout dispersal into account for successful restoration. Dispersal of YOY trout was investigated at the end of the first growing season in a stream in northern Sweden where the former trout population had been depleted. Trout eggs from eight families were stocked in three stocking points in March 2015. In August and September 2015 the trout were located by the means of electrofishing. Body length was measured and tissue samples were collected from the anal-fin. A DNA analysis using Single Nucleotide Polymorphism (SNP) markers was conducted to confirm origin of the individuals. More individuals were dispersed downstream than upstream and the majority of the individuals stayed within a distance of 200 m from the stocking point. Body length and dispersal direction did not have any effect on the distance dispersed. Only one of the families showed a different dispersal pattern than the others, individuals did not stay in the direct vicinity of the stocking point and were aggregated further downstream than other families. Habitat characteristics were found to have an impact on the number of trout located at specific stream sections and on the dispersal distance. These findings can make restoration projects more successful as they facilitate trout managers to find strategic egg stocking points.